Medicine Meets Science: The Imperative of Scientific Research and Publishing for Physician-Scientists - Sonu M.M. Bhaskar (Indian Journal of Radiology and Imaging)
Physician-scientists serve as conduits between clinical practice and scientific research, leveraging their unique expertise to improve patient care and drive medical innovation. This article highlights the indispensable role of research and publishing in promoting evidence-based practices, facilitating professional growth, and shaping public health policy. Drawing on historical and contemporary examples, I examine the challenges faced by physician-scientists, such as ethical dilemmas and declining engagement in research, particularly in resource-constrained settings. I suggest pragmatic strategies to overcome these barriers, emphasizing the need for systemic support, ethical integrity, and the equitable dissemination of advancements. This piece aims to inspire a new generation of physician-scientists to engage deeply with both clinical and research domains, thus advancing global health equity and resilience.